Salinity tolerance of introduced South American sailfin catfishes (Loricariidae Pterygoplichtys GILL 1858) - Brion, Marco Alberto; Guillermo, Jose Gil Jr.; Uy, Cheston; Chavez, Joel; Carandang, Jose Santos IV (2013)
The ecological distribution of species is limited by its physiological tolerances towards natural physical barriers. The experimental LC50 of salinity to an introduced freshwater fish was determined as it implies to its dispersal and distribution. South American sailfin catfishes belong to a freshwater fish family but introduced specimens have been collected in brackish waters of the Pasig River in the Philippines. Tolerance to salinity of this introduced fish could mean increased potential to expand its range into or via marine waters. Juvenile South American sailfin catfishes were purchased from local petshops and were subjected to a 96-hour toxicity test for salinity in the laboratory. Replicated tests using various salinity concentrations were performed. Mortality and survival of test samples were tabulated to determine LC50.The LC50 of salinity was calculated to be 10.6 g/L. Survival analysis of the data gives an estimate that at 10 g/L concentration over 50% of the samples have strong chance of survival beyond 85 hours of exposure to saline water. Post mortem identification of samples confirms they belong to genus Pterygoplichthys. We discuss the implications of the LC50 results on the migration and dispersal of this introduced freshwater fish, and the application of taxonomic data in the study of invasions.
Keywords: Fish contamination; Effect of saline waters on fishes